Audit Sistem Informasi Menggunakan Framework COBIT 4.1 Pada Badan Kependudukan dan Keluarga Berencana Nasional - Ispandi Ispandi; Gilang Purnama Adji; Adjat Sudradjat; Rino Ramadan; Suhardjono Suhardjono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
National Population and Family Planning Agency is one of the government agencies that implements an information system for its operations. Therefore, the National Population and Family Planning Agency requires a management system that is in accordance with the existing infrastructure. Therefore, this study aims to measure the quality of information system management that focuses on procurement, management, and maintenance. Referring to the problems that occurred, the appropriate problem formulation for this research is to carry out an information system audit with the COBIT 4.1 framework and use the Delivery and Support (DS) domain, which in this study are: DS1, DS2, DS3, DS4, DS5, DS10 and DS13. After the audit process is complete, it will get the current maturity value (current maturity level), expected maturity level (expected maturity level) and value (GAP). DS13 became the domain with the highest acquisition value of maturity level with a value of 3.95, while DS3 became the lowest domain with the acquisition of a maturity level value of 3.37. The final result of the audit process that has been carried out is that the current maturity level is 3.61 which is included on a scale of 4 or Managed and Measurable with an expected maturity level of 3.5. So in this study there is no GAP between Current Maturity Level and Expected Maturity.